Pregabalin and Pain After Total Knee Arthroplasty: A Double-Blind, Randomized, Placebo-Controlled, Multidose Trial. Issue 2 (April 2016) - YaDeau, J. T.; Lin, Y.; Mayman, D. J.; Goytizolo, E. A.; Alexiades, M. M.; Padgett, D. E.; Kahn, R. L.; Jules-Elysee, K. M.; Ranawat, A. S.; Bhagat, D. D.; Fields, K. G.; Goon, A. K.; et al.
Abstract : Surv Anesthesiol 2016;60(2):87–88 Approximately 45% of patients experience moderate-to-severe chronic pain after total knee arthroplasty (TKA). Although pregabalin has been shown to reduce postoperative TKA pain, it is only effective at doses of 300 mg or greater daily, which may increase adverse effects such as sedation and confusion.